Carboxyl-modified poly(vinyl alcohol)-crosslinked chitosan hydrogel films for potential wound dressing. (10th July 2015) - Zhang, Di; Zhou, Wei; Wei, Bing; Wang, Xin; Tang, Rupei; Nie, Jiemin; Wang, Jun
Graphical abstract: Highlights: Biocompatible crosslinking agent was chosen for preparation of PVA-COOH/CS hydrogel films. The mechanical performance of cross-linked PVA-COOH/CS hydrogel films was greatly improved. Cross-linked PVA-COOH/CS hydrogel films had no cytotoxicity and hemolytic potential. These hydrogel films showed sustained drug release and improved anti-bactericidal properties. Abstract: The objective of this study was to develop a novel carboxyl-modified poly(vinyl alcohol)-crosslinked chitosan hydrogel films for potential wound dressing. To prepare the crosslinked hydrogels, poly(vinyl alcohol) (PVA) was grafted with succinate acid to yield carboxyl-modified poly(vinyl alcohol) (PVA-COOH). Hydrogel films based on PVA-COOH and chitosan (CS) at different concentrations were crosslinked through the formation of amide linkages. The mechanical properties of these crosslinked hydrogel films in dry and swollen state were greatly improved with high swelling ratio. Water vapor and oxygen permeability evaluations indicated that crosslinked hydrogel films could maintain a moist environment over wound bed. Biocompatibility test showed the crosslinked hydrogels had no cytotoxicity and hemolytic potential. Gentamicin sulfate-loaded crosslinked hydrogel films showed sustained drug release profile, and could effectively suppress bacterial proliferation and protect wound from infection.